Untying the Gordian Knot: on Tanais novaezealandiae Thomson (Crustacea, Tanaidacea, Tanaidae) from New Zealand, with descriptions of two new Zeuxoides species - Bird, Graham J (Zootaxa, 2008)
Tanais novaezealandiae Thomson, 1879 is redescribed based on material from the type locality and re-assigned to the genus Zeuxo. The taxon Anatanais novaezealandiae sensu Sieg from the subantarctic Auckland Islands is a distinct species and requires new material to fully assess its taxonomy. Two new species which could be confused with Z. novaezealandiae, Zeuxoides aka sp.nov. and Zeuxoides rimuwhero n.sp., are described. Both show a close resemblance to some newly-described Australian species and Zeuxoides helleri and support the view that the Australasian/New Zealand region is a hot-spot for species richness within the Tribe Anatanaini. The confused taxonomy of the Subfamily Tanainae is remarked on, with a new phylogenetic review desirable.